A user guide to Mali Africa research in sustainable intensification for the next generation (Africa RISING) baseline evaluation survey data - Azzarri, Carlo; Haile, Beliyou; Howard, Patrice; Roberts, Cleophelia; Initiative for the Development of Africa; Enkhbayar, Sundui; Signorelli, Sara (International Food Policy Research Institute, 2016)
The Mali Africa Research in Sustainable Intensification for the Next Generation (Africa RISING) Baseline Evaluation Survey (MARBES) survey was implemented during May-July 2014 as part of IFPRI’s Monitoring and Evaluation (M&E) of Africa RISING. The Africa RISING program aims to create-through action research and development partnerships-opportunities for smallholder farmers in Africa south of the Sahara to sustainably intensify their farming systems and to improve their food, nutrition, and income security. Initiated in 2012, the program is supported by the United States Agency for International Development (USAID) as part of the U.S. government’s Feed the Future (FTF) initiative. As part of the program, the International Institute of Tropical Agriculture (IITA) leads a sustainable intensification effort focusing on the cereal-based farming systems in the Guinea Savannah Zone of West Africa (Ghana and Mali) and East and Southern Africa (Malawi, Tanzania, and Zambia) while the International Livestock Research Institute (ILRI) leads the research activities focusing on the crop-livestock systems of the Ethiopian highlands. The International Food Policy Research Institute (IFPRI) has been tasked with M&E of the three projects. Mali Africa RISING is being implemented in Bougouni, Yanfolila and Koutiala cercles (the cercle is a type of administrative region), in the Sikasso region of Mali, within the FTF Zones of Influence. The research activities are led by IITA, the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT), ILRI, the Asian Vegetable Research and Development Center (AVRDC), and the International Center for Research in Agroforestry or World Agroforestry Center (ICRAF), as well as local partners: L’Association Malienne d’Eveil et de Développement Durable (AMEDD), l'Association Malienne pour la Sécurité et la Souveraineté Alimentaires (AMASSA), and Mouvement Biologique du Mali (MOBIOM). MARBES collected detailed household- and plot-crop level data addressing various topics: employment (agricultural and non-agricultural); health; agricultural land; crop inputs, harvest, storage, and sale; livestock ownership, feed, and water; agriculture-related challenges and coping strategies; credit and off-farm income sources; housing conditions and ownership of various durable assets; subjective welfare and food security; household-level food consumption; non-food expenditure; agricultural shocks; and child and women anthropometry. The community survey collected data on access to basic services; access to extension services; social organizations, mobility, and village-level shocks; access to natural resources; metric conversion units; and prices of crops and food items. MARBES covered 705 households and 20 communities drawn from the three project cercles. Data was collected using structured questionnaires in multiple local languages through Computer Assisted Personal Interviewing, using the Census and Survey Processing System (CSPro).